2011
DOI: 10.7745/kjssf.2011.44.2.297
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Pyrite Oxidation by Formation of Iron Hydroxide and Fe(III)-silicate Complex under Highly Oxidizing Condition

Abstract: Acid drainage generated by pyrite oxidation has caused the acidification of soil and surface water, the heavy metal contamination and the corrosion of structures in abandoned mine and construction sites. The applicability of Na-acetate (Na-OAc) buffer and/or Na-silicate solution was tested for suppressing pyrite oxidation by reacting pyrite containing rock and treating solution and by analyzing solution chemistry after the reaction. A finely ground Mesozoic andesite containing 10.99% of pyrite and four types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Huang and Evangelou found that PO 4 3− can inhibit the pyrite oxidation by forming ferric phosphate coatings in KH 2 PO 4 and H 2 O 2 solution. Furthermore, Kargbo et al showed that phospholipid can suppress the pyrite oxidation in the presence of silicate, where the Fe‐silicate complex is formed on the pyrite surface to impede the oxidation of pyrite . Afterward, Evangelou et al proved that ‐Fe(II)HCO 3 + or ‐Fe(II)SSCOOFe 2+ may be formed on the pyrite surface in a humidified CO 2 environment.…”
Section: Pyrite Oxidationmentioning
confidence: 99%
“…Huang and Evangelou found that PO 4 3− can inhibit the pyrite oxidation by forming ferric phosphate coatings in KH 2 PO 4 and H 2 O 2 solution. Furthermore, Kargbo et al showed that phospholipid can suppress the pyrite oxidation in the presence of silicate, where the Fe‐silicate complex is formed on the pyrite surface to impede the oxidation of pyrite . Afterward, Evangelou et al proved that ‐Fe(II)HCO 3 + or ‐Fe(II)SSCOOFe 2+ may be formed on the pyrite surface in a humidified CO 2 environment.…”
Section: Pyrite Oxidationmentioning
confidence: 99%